Pengembangan Media Pembelajaran Materi Struktur Atom Berbasis STEM Berbantuan Articulate Storyline 3 di SMA : Penelitian - Anjelli Quratul Ayni; Epinur; Fuldiaratman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purposeofthis research is to determine the development process, feasibility by media and material experts, teacher assessment, and student responses to STEM-based learning media on atomic structure developed with articulate storyline 3. The research method used is Research and Development (R&D) with the Lee & Owens (2004) development model, which consists of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The instruments used are interview sheets and questionnaires. The data analysis techniques used are qualitative data analysis and quantitative data. The results of this study indicate that the interactive STEM-based learning media assistedby articulate storyline 3 achieved feasibility based on validation by material and media experts at percentages of 93,4% and 91,2%. It received a rating from teachers of 92,2% and student responses to the interactive learning media with a percentage of 89,69%. Based on the results of esearch on the development of learning media for atomic structure material based on STEM assisted by Articulate Storyline 3,this media is suitable for use as a learning tool in chemistry education.